The Courage to Be and Types of Anxiety in the Theological Metaphysics of Paul Tillich - Marius CUCU; Oana LENȚA (Eon)
The metaphysical theology proposed by Paul Tillich offers the perspective of a constant connection between the human existential journey and the problem of Non-Being. Centered on the idea of Being, both metaphysics and theology seem to place the issue of Nothingness, of Emptiness, in the background. In reality, the dialectic between Being and Non-Being constitutes the central dynamic for the entire evolution of existence and, likewise, of human thought. Confrontation with Non-Being becomes one of the most important sources of reflection and fundamental ontic experiences. From Non-Being arises anxiety, manifesting in multiple forms that appear equally devastating to our consciousness. A natural question would be: how did those in the past overcome anxiety, and how can we do so today? Paul Tillich believes we are mistaken. Anxiety cannot truly be overcome; instead, it can and must be assimilated—otherwise, convulsive despair could overwhelm the consciousness.